Experimental Research on Mechanical and Energy Characteristics of Reinforced Rock under Dynamic Loading - Xinxi Liu; Yu Li; Fujun Zhao; Yanming Zhou; Weiwei Wang; Shengnan Li (Shock and Vibration)
The properties of anchored surrounding rock may vary considerably under complex geological and stress conditions, especially dynamic loading in deep mining. Therefore, comprehensive study of the reinforced mechanism is required to prevent failures associated with deep mining. In this paper, with sandstone as matrix and steel bar as bolt, the dynamic compression test of reinforced rock was carried out by using a 50 mm rod diameter split Hopkinson pressure bar (SHPB) test device. The mechanical and energy characteristics of reinforced rock under dynamic loading were analyzed. The results show that the dynamic strength of reinforced sample is greater than that of unreinforced sample and increases with the increase of the strain rate. The reflected energy and absorbed energy increase with the increase of incident energy, while the transmitted energy increases slightly. The higher the strain rate, the larger the energy dissipation rate and the higher the degree of fragmentation. It shows that the energy dissipation characteristic reflects the internal damage process to some extent. Compared with the results of unreinforced samples, the reflected energy of reinforced samples significantly increases and the absorbed energy will significantly decrease. It can be seen that the bolt can reduce absorbed energy of surrounding rock, thereby improving the stability of roadway surrounding rock. The results may provide reference for the stability of deep roadway and support design.